Primeiro registro de Molossus coibensis (Chiroptera: Molossidae) na Amazônia Brasileira - Corrêa da Costa, Lanna Jamile; Gonçalves de Andrade, Fernanda Atanaena; Uieda, Wilson [UNESP]; Gregorin, Renato; Barroncas Fernandes, Marcus Emanuel (My University, 2013)
This study reports on the occurrence of Molossus coibensis J. A. Allen, 1904, in the Brazilian Amazon and the second record of this species from Brazil. It also presents a comparative analysis with other two small-bodied Molossus species that occur in Brazil: M. molossus (Pallas, 1766) and M. aztecus Saussure, 1860. The report is based on 8 females captured in urban areas of the city of Bragança, in the northern Brazilian state of Pará. Morphometric data and the qualitative comparison of morphological features permitted the identification of the specimens as M. coibensis, hitherto known only in Tapirapoan, in the southwestern state of Mato Grosso, west-central Brazil. © SAREM, 2013.
First record of Molossus coibensis (Chiroptera: Molossidae) in the Brazilian Amazon
Keywords: Coiban mastiff bat; New record; Northern Brazil